THE LEGAL PROTECTION OF CHILD AS WITNESS AND/OR VICTIMS OF HUMAN TRAFFICKING IN INVESTIGATION PROCESS (Study Case in Unit Protection of Woman and Children in Batu Police Station) - Oktafiani Hatma Suwoto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTIONOKTAFIANI HATMA SUWOTO, 0910113223, 2013, The Legal Protection of Child As Witness and/or Victims of Human Trafficking In Investigation Process (Case Study Unit Protection of Woman and Children in Batu Police Station), Essay, Criminal Law, Faculty Law, Brawijaya University, Lecturer: Dr. Lucky Endrawati, SH., MH. dan Milda Istiqomah, SH. MTCP, 12 Page. Abstract: This study describes or illustrates well as address issues of legal protection of children as witnesses and/or of human trafficking in the investigation process. Legal protection is a protection given to the subject of the law in the form of legal instruments both preventive and repressive, both written and unwritten. Problems studied are (1) Urgency legal protection of children as victims of trafficking crimes in the investigation process, (2) The legal protection of children as victims of human trafficking in the investigation. The research method used is empirical jurisdiction. Some indicators of legal protection of children as witnesses of human trafficking victims, namely: the role of victims, Position witnesses and victims, non-technical, and technical. Technical indicators include several things, namely: The rooms that used to investigated witness and victims, investigated procedures. Whereas, non-technical indicators include: policy and paradigm of police itself which says that legal protection should be given to children because of the laws governing the protection of children as victims and as perpetrators. The forms of legal protection provided by the Unit Protection of Woman and Child to the victim witness include: the anonymity of witnesses and / or victims, rehabilitation of health, counseling, assistance for witnesses and / or victims of the child, and a exclusive investigated room.Keywords: Protection Law, Child, Victim and/or Witness, Human Trafficking